PERAN KIAI DALAM PENGEMBANGAN PENDIDIKAN MODERN DI PONDOK PESANTREN - Laili Savitri Noor; Ismail Nasar; Irena Novarlia; Mukhamad Anieg; Zulihi zulihi (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2023)
The purpose of this research is to determine the Role of Kiai in the Development of Modern Education in Islamic Boarding Schools. The method used is qualitative research with a literature review approach. The steps in this research include identifying literature sources, such as books, scientific journals, research papers, and other relevant documents related to the research topic. There are several steps that researchers must undertake in this study, including: a. Determining the research topic, b. Finding relevant literature sources, c. Selecting relevant and quality literature sources, d. Reading and evaluating the selected literature sources, e. Organizing data and extracting relevant information, f. Analyzing data, and g. Preparing a research report. The conclusion of this study is that the difference between Salafiyah and Khalafiyah Islamic boarding schools lies in their approach and view of Islamic teachings. Islamic boarding schools have many advantages and benefits for students in developing themselves. They provide a comprehensive and in-depth learning experience, as well as preparing students to live independently and contribute to society. The leadership style of Kiai has characteristics that can help develop Islamic boarding schools effectively. The transactional and transformational leadership applied by Kiai can bring Islamic boarding schools to a higher level of quality education. Additionally, effective leadership characteristics of Kiai can create a conducive environment for students to learn, for teachers to engage and grow, and for community support to help improve the quality of education provided by the Islamic boarding schools.